Kształcenie i doskonalenie nauczycieli w globalizującym się społeczeństwie = Education and in-service training of teachers in the globalizing society - Kędzierska, Barbara; Potyrała, Katarzyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is an attempt to synthetize contemporary conditions of teachers` education and in-service training. The starting point of the undertaken deliberations is the influence of globalization on different spheres of life with special attention drawn to educational processes at the university level. The chosen contexts of contemporary culture as well as the change in the status of information become a conceptual background for the transformation of former, traditional model of teachers` education (teaching) towards the model based on communication, cooperation and taking action (learning).
Keywords: kształcenie nauczycieli; doskonalenie nauczycieli; globalizacja